2014
DOI: 10.1088/0022-3727/47/18/185201
|View full text |Cite
|
Sign up to set email alerts
|

PECVD RF versus dual frequency: an investigation of plasma influence on metal–organic precursors' decomposition and material characteristics

Abstract: Plasma enhanced metal organic chemical vapor deposition (PEMOVCD) of titanium nitride with dual frequency plasma sources were studied by means of plasma and material characterization. Adding a low frequency to a radio frequency plasma in order to enhance the deposition reaction mechanism is demonstrated. An in depth investigation of plasma by optical emission spectroscopy shows that due to secondary electrons heating the plasma, it enters a gamma-mode and that LF permits better dissociation of the H 2 reactant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The selective depositions are realized in a reaction chamber included a pulsed liquid injection system for precursors vaporization and plasma assistance on 200 and 300 mm wafers. 29 This versatile tool allows the deposition of oxides, metal nitrides in CVD, PECVD, ALD, or PEALD modes. [29][30][31] The deposition module consists of an evaporating furnace and a deposition chamber.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selective depositions are realized in a reaction chamber included a pulsed liquid injection system for precursors vaporization and plasma assistance on 200 and 300 mm wafers. 29 This versatile tool allows the deposition of oxides, metal nitrides in CVD, PECVD, ALD, or PEALD modes. [29][30][31] The deposition module consists of an evaporating furnace and a deposition chamber.…”
Section: Methodsmentioning
confidence: 99%
“…29 This versatile tool allows the deposition of oxides, metal nitrides in CVD, PECVD, ALD, or PEALD modes. [29][30][31] The deposition module consists of an evaporating furnace and a deposition chamber. The furnace is used for the flash vaporization of the liquid precursor.…”
Section: Methodsmentioning
confidence: 99%
“…It is also well known that the ion flux influences the compressive to tensile stress transition in dual frequency PECVD deposited SiN films 40 . In a previous study, we have shown that the growth rate, density and resistivity of a PECVD TiN film deposited in a dual frequency CCP plasma reactor can be tuned by adjusting the low frequency to high frequency power ratio, which modulates the ion energy in the discharge 41 . This regime thus allows gap filling of trenches or vias by PECVD [42][43][44] .…”
Section: Pecvd Process: Ions Versus Radicalsmentioning
confidence: 99%
“…Hence, several experimental investigations have been pursued to get a well-crystallized titania layer at low substrate temperature. Among them, we can cite few articles where process parameters such as the Ti precursor (Titanium tetrachloride TiCl4,Titanium tetraisopropoxide TTiP, Tetrakis(dimethylamido)titanium(IV) TDMAT, Titanium ethoxide Ti(OEt)4), precursor dilution [19,20], [21], plasma gas composition [22] (Ar, O2, H2, N2 and mixtures), plasma configuration (direct or remote [23]), excitation frequency [24] (Low frequency [25],…”
Section: Introductionmentioning
confidence: 99%